1986
DOI: 10.1103/physreva.33.2612
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation and distribution of macroscopic order in formation processes of a dissipative structure

Abstract: %e report the temporal developments of the variance and distribution of fluctuations of macroscopic order in a structure-formation process using an electrohydrodynamic instability of a nematic liquid crystal at f& f"where f and f, are the applied and the critical field frequencies separating two different instabilities: a convective flow instability and a forced oscillatory instability of the director. At f & f" the dissipative structure appears essentially as the forced oscillatory instability of the director… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…, the streamlines and the director field, although time dependent in the form of a standing wave, consist of convection rolls with a maximum of the amplitude in the middle of the cell. This statement does not seem to agree with some experimental observations [6,7]. Moreover, even the qualitative nature of the underlying instability mechansism as proposed in Refs.…”
Section: Introductionmentioning
confidence: 43%
See 2 more Smart Citations
“…, the streamlines and the director field, although time dependent in the form of a standing wave, consist of convection rolls with a maximum of the amplitude in the middle of the cell. This statement does not seem to agree with some experimental observations [6,7]. Moreover, even the qualitative nature of the underlying instability mechansism as proposed in Refs.…”
Section: Introductionmentioning
confidence: 43%
“…In the first one, particle trajectories have been observed. This was done by visual inspection of the flow, looking from the side into the boundary layer of an open cell [6]. At these boundaries, one must expect the director field to be fairly complicated because of inhomogeneities of the electric field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillatory behaviour of director structures in the dielectric regime was established already in early experiments [7,8]. In a study of DR using stroboscopic illumination, Schneider et al [9] have shown experimentally that the amplitudes of optical contrast are strongly time dependent as a consequence of the dynamics of the director field.…”
Section: Introductionmentioning
confidence: 96%
“…However, more realistic models of physical systems require considering various noise sources, for example, the laser models [10], the lattice model [11], the structure-formation process in liquid crystals [12], the imperfect pitchfork bifurcation in superfluid turbulence in liquid helium [13], etc. Though various sources are presented simultaneously in some stochastic processes, they are assumed to have different origins and are treated as independent random variables in most of the previous investigations [10 -15].…”
mentioning
confidence: 99%